Classification of Loan Applications of Garima Bikas Bank Ltd Using Decision Tree Classification Method - Shrestha, Subik; Paudel, Laxman (Journal of Advanced College of Engineering and Management, 2019)
There is a possibility in finding hidden patterns that might help find a relationship between the information provided by the Loan Applicants during the Loan Application process and the status of their loan repayment. This paper highlights on finding such patterns by building a Decision Tree with the help of the data provided during the loan application process. Eleven attribute information of Five Hundred sixty four loan applicants were collected from Garima Bikas Bank Ltd. A decision tree model with a depth of 6 has been built by calculating the entropy and information gain at each split and selecting the feature with the highest information gain.